THE EFFECT OF APPLICATION TOWARDS CADETS’ ENGLISH ABILITY: A GREEN PLANET SUISTAINABILITY - Irma Shinta Dewi; Fatimah; Endah Fauziningrum (Jurnal Maritim Malahayati, 2023)
There are many things should be prepared for the Human Resource (HR), to guarantee the promise future and career. The 5.0 era hopes that technology and human are going to live harmoniously in order to improve the quality of human life on an ongoing basis and facilitate the human interest. Meanwhile, in 4.0 era, the social ecosystem accesses a database in cyberspace from the internet and searches, retrieves and analyzes information or data. The society 5.0 is very dependent on cyberspace (visual room) and physical space. In this era, the English ability is very important to achieve. Moreover, there should be any efforts to improve it. The purpose of this study is to describe the efforts of maritime educational institutions in facing the 5.0 era using applications affecting the cadet’s competence of English at PIP Semarang. This type of research is quantitative method with ‘one group pre-test post-test pre-experimental (non-design)’. To complete the data, it could be done by using observation, documentation and library research. Meanwhile the analysis of research data used validity and reliability. The results of the study showed that an application has affected to improve the cadet’ English ability. The conclusion is the application is one of the efforts of maritime education to face 5.0 era in education technology as consequently green planet sustainability.